Dengue Vectors Surveillance in Endemic Areas in Kuala Lumpur City Centre and Selangor State, Malaysia - Chen, C.D.; Seleena, B.; Nazni, W.A.; Lee, H.L.; Masri, S.M.; Chiang, Y.F.; Sofian-Azirun, Mohd (2006)
An ovitrap-based study was initiated to determine the distribution and abundance of dengue vectors, Aedes aegypti and Aedes albopictus, in four residential areas, Taman Samudera (Gombak, Selangor), Kampung (Kg.) Banjar (Gombak, Selangor), Taman Lembah Maju (Cheras, Kuala Lumpur) and Kampung (Kg.) Baru (City centre, Kuala Lumpur). Kg. Baru gave the highest ovitrap index in both indoors and outdoors, 89.29 and 82.35, respectively. Kg. Baru also gave the highest mean number of Ae. aegypti and Ae. albopictus per ovitrap in both indoors and outdoors, compared to Taman Samudera, Kg. Banjar and Taman Lembah Maju. However, the statistical analysis showed that outdoor population of Ae. aegypti in 4 study sites was not significantly different from each other (P>0.05). The indoor population of Ae. aegypti, and indoor and outdoor population of Ae. albopictus from Kg. Baru were significantly more than other sites by 1.41- to 488.50-folds (P<0.05). This study implicates that Ae. albopictus is the dominant outdoor breeder, and it prefers outdoor conditions with more vegetation as observed in Taman Lembah Maju and Kg. Baru. However, Taman Samudera and Kg. Banjar, which are located in rapidly developing areas and have less vegetation, showed less population of Ae. albopictus than Ae. aegypti even outdoors.